Blood Pressure and Aerobic Capacity Profile Based on 6 MWT - Nafiah Nafiah (Health Media, 2026)
Blood pressure and aerobic capacity are important indicators of cardiovascular health and functional capacity in physiotherapy practice. Simple and practical screening methods include blood pressure measurement and the Six-Minute Walk Test (6MWT). This study aimed to describe blood pressure and aerobic capacity based on the 6MWT among patients at Nafaya Centre, Banjar Regency, from February to June 2026. A descriptive study with a cross-sectional design was conducted involving 28 respondents selected using the total sampling technique. The observed variables included age, sex, blood pressure, heart rate, 6MWT walking distance, VO₂max, and Metabolic Equivalents (METs). The results showed that the mean age of the respondents was 45.9 ± 13.8 years, with the majority being adults (64.3%). The mean systolic and diastolic blood pressures were 124.4 ± 13.7 mmHg and 79.6 ± 11.6 mmHg, respectively. The mean 6MWT distance was 501 ± 62 meters, with a mean VO₂max of 19.03 ± 2.11 mL/kg/min and a mean METs value of 5.44 ± 0.60. Most respondents had low aerobic capacity (64.3%), while 35.7% had moderate aerobic capacity. These findings suggest that blood pressure measurement and the 6MWT are useful as simple screening methods for assessing cardiovascular health and functional capacity.